Mass-Like Extreme Wall Thickening of the Entire Common Bile Duct in a Case of Portal Cavernoma Cholangiopathy - Veeraraghavan Gunasekaran; Supraja Laguduva Mohan; Sunitha Vellathussery Chakkalakkoombil; Kuppusamy Senthamizhselvan (Thieme Medical and Scientific Publishers Pvt. Ltd., 2022)
Portal cavernoma cholangiopathy (PCC) refers to the cholangiographic abnormalities that occur in patients with portal cavernoma. These abnormalities may be either due to chronic portal vein thrombosis or extrahepatic portal vein occlusion. These abnormalities occur due to enlargement of the bridging tortuous paracholedochal, epicholedochal, and cholecystic veins exerting pressure on the bile ducts. Ischemic changes can also occur in the bile duct due to portal vein thrombosis, which affects the microvascular circulation or associated hepatic artery thrombosis. These may be either reversible with shunt procedures such as transjugular intrahepatic portosystemic shunt (TIPS) or irreversible in the advanced stage, leading to recurrent episodes of biliary pain, cholangitis, and cholestasis. Occasionally it may present as mass-like diffuse common bile duct (CBD) wall thickening, which may be confused with mimickers like primary CBD lymphoma, immunoglobulin G4-related sclerosing cholangitis, and even cholangiocarcinoma on imaging. Thus, we need to be aware of the mass-forming PCC imaging findings to avoid unnecessary invasive procedures like biopsy or surgical intervention. Here, we present a case of PCC, which presented as mass-like diffuse CBD wall thickening with patent lumen on ultrasound that led to further workup with contrast-enhanced computed tomography and magnetic resonance imaging. The wall thickening showed persistent delayed enhancement, no significant diffusion restriction, and there was also associated superior mesenteric vein thrombosis with multiple mesenteric collaterals. A positron emission tomography-CT scan also ruled out malignant disease as there was no uptake. Finally, a diagnosis of mass-forming PCC was made by combining imaging features and excluding other causes.